OPTIMIZING PRODUCTIVITY AND QUALITY MANAGEMENT AT UD SALMA JAYA: STRATEGIES FOR ADDRESSING MACHINE BREAKDOWNS AND OPERATIONAL CHALLENGES - Tania Meligiatri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The food and beverage (F&B) industry plays a significant role in Indonesia’s economy, contributing substantially to the manufacturing sector's growth. However, small and medium-sized enterprises (SMEs) in this sector often face challenges related to production capacity and product consistency, limiting their ability to meet rising market demand. UD Salma Jaya, an SME specializing in snack production, implemented automation to enhance efficiency but encountered machine failures that disrupted operations. These breakdowns led to decreased productivity and inconsistent product quality, particularly when reverting to manual production. This study aims to identify the root causes of these operational challenges and evaluate strategies for optimizing productivity and product quality. Using Root Cause Analysis (RCA), the Fishbone Diagram, and the Analytic Hierarchy Process (AHP), the study assesses whether investing in new automation technology or improving manual production methods would be the most effective solution. The findings suggest that upgrading machinery while enhancing workforce adaptability through targeted training programs can ensure long-term operational stability. This research provides valuable insights for SMEs facing similar automation-related challenges in the F&B industry.